Architectural details - windows - Braun ([S.l.] : Verlagshaus Braun, 2008)
Windows serve as the eye of the house. They provide contact between the internal world of a building and the world outside ? windows permit light, air and glances to move into the space but also establish a connection to the outer world for all people ins.